2018
DOI: 10.1002/mma.4897
|View full text |Cite
|
Sign up to set email alerts
|

Horospherical coordinates for optimal Cosserat microrotations

Abstract: MSC Classification: 53A35; 53C22; 53C80; 74B20; 74N15 This note proposes the use of horospherical coordinates to overcome the problems associated with multiple eigenvalues occurring in the Cosserat microrotation problem. The advantages of this coordinate system are argued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In the works of Eremeyev et al 5 and Eringen and Maugin, 6 the concept of elastic Cosserat continua can be found well explained. Recently, horospherical coordinates for optimal Cosserat microrotations have been discussed by Rau 7 . Through the suggested theory, complexity and heterogeneity inherent in materials can be described by considering microstructure of material, e.g., magnetic materials and granular materials.…”
Section: Introductionmentioning
confidence: 99%
“…In the works of Eremeyev et al 5 and Eringen and Maugin, 6 the concept of elastic Cosserat continua can be found well explained. Recently, horospherical coordinates for optimal Cosserat microrotations have been discussed by Rau 7 . Through the suggested theory, complexity and heterogeneity inherent in materials can be described by considering microstructure of material, e.g., magnetic materials and granular materials.…”
Section: Introductionmentioning
confidence: 99%